Hubungan Jenis Kelamin dan Usia dengan Kesehatan Mental di Kalangan Siswa Sekolah Menengah Atas di Kota Bukittinggi - Bella Lucintarillova Arif Lubis; Dianni Arma Wahyu Setia Ningsih; Nomira Putri; Khalisah Muthmainnah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Abstract: Mental health conditions in adolescent groups are important in the psychosocial development of adolescents. A group of mentally healthy teenagers is a valuable investment and asset for human resources in a country. Mental health is an important aspect in realizing overall health. Adolescence is an important period for developing social and emotional habits that are important for mental well-being. The aim of this research is to determine the picture of mental health in groups of teenagers in senior high schools in Bukittinggi city. The design of this research is an observational study with a cross sectional design. This research was conducted at a high school in Bukittinggi City with a total sample of 118 people taken based on the multistage stratified clustered sampling method. The results of the study showed that there was no relationship between age and gender on the mental disorders of high school students in Bukittinggi City (p>0.05).